ТАЛАБАЛАР КРЕАТИВ КОМПЕТЕНЦИЯСИНИ РИВОЖЛАНТИРИШ ҲАҚИДА - Ибраймов, Ы.Е. (SCIENCE and SOCIETY, 2023)
The article describes the creation of favorable pedagogical conditions for the training of qualified future specialists, the introduction of advanced pedagogical technologies into the educational process, the development of students' creative competencies are the part of the future professional competence.
Keywords: education; creativity; competence; teacher; student; TRIZ; ability